2012
DOI: 10.12693/aphyspola.121.694
|View full text |Cite
|
Sign up to set email alerts
|

Light Scattering Studies of Hydration and Structural Transformations of Lysozyme

Abstract: We have applied the method of dynamic light scattering to analyse the lysozymeethanol interaction. For low ethanol concentration (below 4.3% (v/v)) no chemical denaturation process is observed. When the ethanol concentration grows above the triggering concentration the hydrodynamic radius of lysozyme increases, indicating the structural changes within the protein molecule. The observed structural modications are attributed to dehydration and preliminary tertiary structure modication of the protein molecule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
(29 reference statements)
1
5
0
Order By: Relevance
“…With the increase in the ethanol concentration, up to about 30% (v/v), the specific volume increases up to the value of 0.726 cm 3 · g -1 . These data are in a good correlation with our observations of the changes of lysozyme hydrodynamic radius, R H (Szymańska & Ślósarek, 2012). According to the data from dynamic light scattering R H remains constant and equals (1.856±0.023) nm when the ethanol concentration increases up to about 4.3% (v/v) and then starts to increase with a growing amount of alcohol.…”
Section: Resultssupporting
confidence: 90%
“…With the increase in the ethanol concentration, up to about 30% (v/v), the specific volume increases up to the value of 0.726 cm 3 · g -1 . These data are in a good correlation with our observations of the changes of lysozyme hydrodynamic radius, R H (Szymańska & Ślósarek, 2012). According to the data from dynamic light scattering R H remains constant and equals (1.856±0.023) nm when the ethanol concentration increases up to about 4.3% (v/v) and then starts to increase with a growing amount of alcohol.…”
Section: Resultssupporting
confidence: 90%
“…R h of Lyz was determined to be 23 Å. This is larger than 18–19 Å often reported in the literature . These values are almost always reported at pH 4.5 in solutions containing at least 0.1 M salt.…”
Section: Resultsmentioning
confidence: 48%
“…This is larger than 18-19Å often reported in the literature. 67,68 These values are almost always reported at pH 4.5 in solutions containing at least 0.1 M salt. Esposito et al 69 found that R h was only 6Å at pH 3 in the presence of 4 mM NaCl.…”
Section: Size and Protein-protein Interactionsmentioning
confidence: 79%
“…* MZ, NAD, KETO and BSA formulations were also prepared with 1 % of PEG6000 and 0.3 % of trehalose for freeze-drying. (Avdeef, et al 2000;Sheng, et al 2006;Singhai, et al 1996;Zhou, et al 2005) NAD* 309 8.3 (25 °C), 8.3 (pH 7) 9.28 + 1.7 (Avdeef and Berger 2001;Zhou, et al 2005) MZ* 171 10.5 (25 °C), 10.5 (pH 7) 2.38 ø 2 (Kim, et al 2012;Wu and Fassihi 2005;Zhou, et al 2005) BSA* 6.65x10 4 40 4.6 -4.8 -~ 7 1 (Sigma-Aldrich; Yohannes, et al 2010) LZ 1.47x10 4 >10 11.1 + ~ 3.7 0.5 (Fritz, et al 1995;Szymańska and Ślósarek 2012) FITC-DEX 4000 50 ø ~ 2.8 1 (Sigma-Aldrich) † 40.7 mg/ml solubility at pH 7 was used for the calculation of diffusion coefficients of KETO with the Hiquchi equation. Excess KETO remained in the crystalline form in the hydrogel at 3.4%, and therefore in practice initial drug concentration ˃ drug solubility.…”
Section: Preparation Of the Anfc Hydrogel Formulationsmentioning
confidence: 99%